Intermuscular Lipoma in Dogs - Huppes, Rafael Ricardo; Pietro, Natália Dal; Wittmaack, Mônica Carolina; Sembenelli, Guilherme; Bueno, Cynthia Marchiore; Pazzini, Josiane Morais; Jark, Paulo César; De Nardi, Andrigo Barboza; Castro, Jorge Luiz Costa (Acta Scientiae Veterinariae, 2016)
Background: Lipoma is a benign tumor composed of mature adipose tissue commonly found in subcutaneous tissues. However, eventually, lipomas may be located between the muscle fasciae being classifed as intermuscular lipomas. Complete surgical resection of the tumor mass is indicated as a treatment of affected patients.This report describes fve cases of intermuscular lipoma in dogs, due to the scarcity of data in the literature and lipoma relative importance in the clinical and surgical routine. Case: Five dogs were presented with a history of a large volume in the limbs with progressive growth, suggesting the presence of neoplasia. The frst step was to conduct anamnesis, when the owner reported slow growth, absence of pain, limping and licking of site. No other change was observed upon physical examination. Complete blood count (CBC) as well as liver assessment (FA) and renal (creatinine) were performed in all patients, and the results showed no changes. Fine needle aspiration cytology (FNAC) was performed and showed cells from adipose tissue, followed by histopathological examination of the lesions. Histopathological examination after incisional biopsy of the tumors showed malignancy-free tissue, composed of adipocytes without atypia, interspersed with fbrovascular stroma, confrming the lipoma diagnosis. Intermuscular lipomas were diagnosed in fve dogs with a history of a large volume in the limbs with progressive growth; all of them underwent bloc resection of the tumors. In all cases, the intermuscular lipomatous tumors were well-circumscribed and easily isolated from the tissues. Discussion: Although lipomas are relatively common in older dogs, especially in the subcutaneous tissue, intermuscular subtype is rare in veterinary medicine, which justifes the report of these cases. Intermuscular lipomas account for only 0.3% of the occurrences in human medicine. Morphologically described as tumors of slow and progressive evolution, typically reaching sizes up to 2 cm in humans, the particular cases of tumor masses greater than 5 cm are called giant lipomas. The slow development of intermuscular lipomas has also been described in domestic animals by, thus corroborating the clini cal history in this work. The intermuscular septum is considered as the origin of intermuscular lipoma, with subsequent development of the adipose tissue between adjacent muscle bundles, thus, resulting usually in well-circumscribed mass of easy surgical divulsion. The morphological characteristics of the resected lipomas, as well as the simple surgical technique corroborate descriptions in the literature. Intermuscular lipomas consist of a challenging diagnosis despite attracting little attention from surgeons. The possibility of the mass being malignant, such as liposarcoma, should also be considered since the clinical symptoms consist of swelling of the deep soft tissues. The diagnosis for all these patients was obtained by histopathological examination, since the simple observation of the clinical fndings alone does not support the tumor diagnosis. Lipoma and liposarcoma should be differentiated by cytological and histopathological evaluations of the neo plasia, whereas infltrative lipomas can be diagnosed based on diagnostic imaging methods or even on the fndings during surgery. In this report, specifcally, the fndings during surgery contributed to the differentiation between infltrative and intermuscular lipoma, while for malignancy rating all patients underwent cytological and histopathological evaluations as indicated in the literature. In conclusion, this study demonstrated that complete resection of intermuscular lipoma proved to be an effective treatment to cure the patients. Keywords: benign neoplasm, surgery, resection of intermuscular, canine.